Daniel's vision of the Son of Man - Young, Edward Joseph, 1907-1968; Tyndale Old Testament lectures, 1958. (London, UK Tyndale, 1958)
Includes bibliographical references.
Keywords: Bible. O.T. Daniel, Apocalyptic passages -- essays, addresses, lectures